WASIAT WAJIBAH BAGI ANAK ANGKAT DALAM RANGKA PERLINDUNGAN HUKUM TERHADAP ANAK (Perspektif Undang-undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak dan Kompilasi Hukum Islam) - Djamal Djamal (Al-Bayyinah, 2018)
The author wants to show that in Law Number 23 of 2002 concerning Child Protection, clearly and in detail regulates the rights of adopted children which must be met by adoptive and biological parents. And in Compilation of Islamic Law gives the right to adopted children to get a third of the inheritance of foster parents to fulfill the rights or life needs of adopted children after their parents die.